2021
DOI: 10.1371/journal.pone.0252993
|View full text |Cite
|
Sign up to set email alerts
|

The Cedar Project: Relationship between child apprehension and attempted suicide among young Indigenous mothers impacted by substance use in two Canadian cities

Abstract: Indigenous leaders are gravely concerned over disproportionate representation of Indigenous children in Canada’s child welfare systems. Forced separation from children is deeply traumatizing for mothers and detrimental to the wellbeing of Indigenous families, communities and Nations. This study examined relationships between child apprehension and suicide attempt within a cohort of young Indigenous women impacted by substance use. We utilized data collected every 6 months (2008–2016) by the Cedar Project, an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…These findings are consistent with previous prospective studies of Indigenous youth in British Columbia that showed that having at least one parent who attended IRS was associated with twice the odds of having been in the care of the CWS compared to youth without familial IRS exposure [ 22 , 23 ]. In this same BC cohort, young Indigenous mothers who reported recent child removal, were more likely to have a parent who attended IRS, and most (70%) had been in CWS care themselves as children [ 24 ]. Moreover, among Indigenous adults from across Canada who were born during the Sixties Scoop era we found that parental IRS attendance increased the odds of spending time in the CWS, and that this relation was mediated by adverse childhood household experiences [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previous prospective studies of Indigenous youth in British Columbia that showed that having at least one parent who attended IRS was associated with twice the odds of having been in the care of the CWS compared to youth without familial IRS exposure [ 22 , 23 ]. In this same BC cohort, young Indigenous mothers who reported recent child removal, were more likely to have a parent who attended IRS, and most (70%) had been in CWS care themselves as children [ 24 ]. Moreover, among Indigenous adults from across Canada who were born during the Sixties Scoop era we found that parental IRS attendance increased the odds of spending time in the CWS, and that this relation was mediated by adverse childhood household experiences [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have empirically explored the link between IRS exposure, subsequent parent-child separations, and distress levels. Existing studies typically comprised non-representative samples of Indigenous adults and/or young people living off-reserve [ 11 , 22 , 23 , 24 ]. The current studies explored the link between intergenerational IRS exposure (i.e., those who had a parent and/or grandparent who attended IRS), parent-child separation, and youth psychological distress in a nationally representative sample of First Nations youth living on-reserve and in northern communities in Canada (Study 1).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is more literature on programmes and policies that have demonstrated effectiveness within non-Indigenous communities, similar analyses have yet to be completed within Indigenous populations. The programmes described in (Perdacher et al, 2019;Gutierrez et al, 2018) Social services -Prioritize Indigenous systems of child welfare with First Nation communities (Haight et al, 2018) -Increase holistic wellness supports for families whose children must be apprehended (Ritland et al, 2021) -Increase accessibility to preventative or alternative sector services rather than child welfare (Sinha et al, 2013) -Income -Provide equitable funding for Indigenous children in child welfare systems (Blackstock, 2016) -Health care -Promote Indigenous-led healthcare partnerships (Allen et al, 2020) -Increase cultural and trauma-informed training in health settings (Cullen et al, 2021;Rizkalla et al, 2020) -Improve access to community-based primary care services (Tompkins et al, 2018; have some support for promoting wellness among Indigenous communities, although more research is required to explore how such programmes can be implemented collaboratively to reduce exposures to ACEs. Among these proposed programmes and strategies, it is likely that it is not the individualization of programmes that will warrant the most benefit within Indigenous communities, but the intersectional implementation of strategies across sectors.…”
Section: Creating Relevant Prevention Policiesmentioning
confidence: 99%
“…Increase holistic wellness supports for families whose children must be apprehended (Ritland et al, 2021)…”
mentioning
confidence: 99%
“…For example, the study by Gebremeskel found the prevalence of suicidal ideation to be high among Eritrean refugees in Tigray, Ethiopia, in particular amongst those with a previous history of trauma, post-traumatic stress disorder, and a family history of mental illness [ 24 ]. Finally, the study by Ritland and colleagues identified a relationship between child apprehension and suicide attempt among a cohort of young Indigenous women in Canada who had been impacted by substance use [ 25 ].…”
Section: Introductionmentioning
confidence: 99%